The Effect of Vitamin D Supplementation on Sputum Conversion in TB Patients: A Literature Review - Desi Afnita Lubis; Sanjay Saputra; Rega Hamdana Simbolon (Riviera Publishing, 2026)
Tuberculosis (TB) remains a major global health challenge, with delayed sputum smear conversion continuing to affect treatment outcomes and disease transmission control. Vitamin D has received increasing attention as an adjunctive therapy in TB management due to its immunomodulatory role in enhancing macrophage activation and antimicrobial responses. However, evidence regarding the effectiveness of vitamin D supplementation in accelerating sputum conversion remains inconsistent across different populations and treatment protocols. This study aimed to evaluate the effect of vitamin D supplementation on sputum smear conversion among pulmonary tuberculosis patients and identify factors contributing to variations in treatment outcomes. A systematic literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies published between 2016 and 2024 were identified through PubMed, Scopus, and Google Scholar databases using predefined keywords related to vitamin D supplementation, tuberculosis, and sputum conversion. Eligible primary studies, including randomized controlled trials, clinical trials, quasi-experimental studies, and observational studies, were analyzed descriptively. The findings revealed heterogeneous results, with several studies demonstrating accelerated sputum conversion following vitamin D supplementation, particularly among patients with baseline vitamin D deficiency and adequate supplementation dosage and duration. However, other studies reported no significant improvement, potentially due to differences in supplementation protocols, patient characteristics, and geographical factors. In conclusion, vitamin D supplementation shows potential as an adjunctive therapy for pulmonary tuberculosis, but current evidence remains insufficient to support universal application. Further standardized clinical studies are required to determine optimal dosage, duration, and target populations.